Latent tuberculosis infection in patients with chronic plaque psoriasis: evidence from the Italian Psocare Registry. (17th March 2015) - Gisondi, P.; Cazzaniga, S.; Chimenti, S.; Maccarone, M.; Picardo, M.; Girolomoni, G.; Naldi, L.; the Psocare Study Group; Griseta, V.; Miracapillo, A.; Azzini, M.; Mocci, L.; et al.
Summary Background The nationwide prevalence of latent tuberculosis infection (LTBI) in Italian patients with psoriasis has never been investigated. Objectives To estimate the nationwide prevalence of LTBI in Italian patients with psoriasis who are candidates for systemic treatment. Methods Data were obtained from the Psocare Registry on those patients (n = 4946) with age > 18 years, systemic treatment at entry specified and tuberculin skin test (TST) performed according to the Mantoux method. LTBI diagnosis was based on a positive TST result in the absence of any clinical, radiological or microbiological evidence of active tuberculosis. Results Latent tuberculosis infection was diagnosed in 8·3% of patients with psoriasis (409 of 4946). The prevalence of LTBI was lower in patients on biologics than in those on conventional systemic treatments, ranging from 4·3% (19 of 444) of patients on adalimumab to 31% (eight of 26) of those on psoralen–ultraviolet A (P < 0·05). Independent factors associated with LTBI were male sex [odds ratio (OR) 1·30, 95% confidence interval (CI) 1·04–1·62; P = 0·02], age over 55 years (OR 2·93, 95% CI 2·18–3·93; P < 0·001) and being entered into a conventional treatment (OR 3·83, 95% CI 3·10–4·74; P < 0·001). Positive history of tuberculosis was seen in 1% of patients (n = 49). Conclusions The nationwide prevalence of LTBI in Italian patients with psoriasis candidate to systemic treatment is high, and screening is recommended prior to biological treatment.